Evaluation of O2SN Achievement Development through Volleyball among Athletes with Speech and Communication Disorders - Amalia Pratidina; Erick Burhaein (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to evaluate the development of athletes achievement through volleyball activities in improving physical abilities, social skills, and self-confidence of students with speech impairments at Special Needs School. The data analysis technique used is the Miles and Huberman model, which consists of data reduction, namely selecting and simplifying data according to the research focus; data display by organizing data in the form of tables, matrices, or narrative descriptions; and conclusion drawing or verification by summarizing the evaluation results based on the CIPP model. The population of this study includes all students with speech impairments at Special Needs School who participate in volleyball training programs. The research sample was determined using purposive sampling, which involves selecting informants based on the consideration that they have in-depth knowledge of the achievement development process. The sample consists of three students with speech impairments who participate in volleyball training, one physical education PJOK teacher as the coach, the school principal as the policy maker, and several parents as sources of additional supporting information. The results show that the objectives of the volleyball learning and coaching program at Special Needs School are aligned with the goals of adaptive physical education, namely developing motor skills, social abilities, and achievement potential of students with intellectual speech impaired. The program is also directed as a means of participation in competitive events such as O2SN. This indicates that, at the policy level, the school has demonstrated a commitment to the development of sports achievement for students with special needs. However, program planning has not been fully developed based on an analysis of individual student needs. The learning program still refers to the general curriculum with limited modifications, so it has not yet fully accommodated the characteristics of intellectual limitations, such as the ability to understand instructions, concentration, and short-term memory capacity.